Psychometric Properties of the Patient Advocacy Scale for Intensive Care Nurses - Mara Ambrosina de Oliveira Vargas; Jennifer Aguilar Leocádio de Menezes; Laura Cavalcanti de Farias Brehmer; Jamila Geri Tomaschewski-Barlem; Silviamar Camponogara; Dulcinéia Ghizoni Schneider; Flávia Regina Souza Ramos; Daniela de Oliveira Cardozo; Elizabeth Peter (SAGE Open, 2023)
Patient advocacy exercised by an intensive care nurse refers to the defense of the patient’s interests and rights and can be measured if, for that, there are valid, reliable and reliable instruments, that is, which have their psychometric properties proven. Therefore, the patient’s advocacy processes would be permanently monitored and evaluated, also, the practice would become more visible. Perform psychometric validation of the Patient Advocacy Scale for Intensive Care Nurses (EAPEnf-ICU). Instrumental research for instrument validation, with exploratory and confirmatory factor analysis. Carried out from January to June 2021 with 377 Brazilian intensive care nurses, selected by non-probabilistic convenience sampling. Data were collected by means of Google Forms, organized on Excel ® 2010 software and analyzed on R software. The Ethics Committee approved the study. Participants received information about the research, agreed to respond to the questionnaire and were guaranteed anonymity. From the scale structural exploration by analyzing exploratory, confirmatory and internal consistency of the measurement instrument, the final version of the EAPEnf-ICU was composed of 54 items, distributed in 5 dimensions/factors: Factor 1—Clinical and organizational advocacy in intensive care; Factor 2—Barriers associated with the intensive care clinical and organizational complexity; Factor 3—Attitudes to promote the autonomy of patients and family members in intensive care; Factor 4—Barriers associated with divergences and ethical-professional limits in intensive care, and Factor 5—Intensive care nurse’s personal and professional background. Findings point that the instrument presented in this study is valid and reliable for assessing the aforementioned construct, as it presents theoretical and empirical consistency, identifying five dimensions related to the exercise of patient advocacy by the intensive care nurse.